1986
DOI: 10.1016/0035-9203(86)90149-5
|View full text |Cite
|
Sign up to set email alerts
|

A simple and economical direct agglutination test for serodiagnosis and sero-epidemiological studies of visceral leishmaniasis

Abstract: A simple and economical direct agglutination test for the detection of visceral leishmaniasis is described. Trypsin-treated, Coomassie Brilliant Blue-stained, formalin-preserved promastigotes were used as antigen in re-usable V-well microtitre plates. In 21 patients with recent kala-azar, titres of 1:51200 or higher were found. Cured kala-azar patients treated 4 to 14 months before testing, showed titres in the range of 1:3,200 to greater than 1:51,200. Healthy and diseased controls had titres below 1:1,600 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
144
2
4

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(155 citation statements)
references
References 10 publications
5
144
2
4
Order By: Relevance
“…The principal phases of the procedure for preparing the DAT antigen were mass production of promastigotes of L. infantum (Iranian strain) in RPMI1640 medium supplemented with 10 % fetal bovine serum, trypsinization of the parasites, staining with Coomassie Brilliant blue and fixing with 2 % formaldehyde (Mohebali et al 2005;el Harith et al 1989;Harith et al 1986). …”
Section: Dat Testmentioning
confidence: 99%
“…The principal phases of the procedure for preparing the DAT antigen were mass production of promastigotes of L. infantum (Iranian strain) in RPMI1640 medium supplemented with 10 % fetal bovine serum, trypsinization of the parasites, staining with Coomassie Brilliant blue and fixing with 2 % formaldehyde (Mohebali et al 2005;el Harith et al 1989;Harith et al 1986). …”
Section: Dat Testmentioning
confidence: 99%
“…4 El Harith and others adapted the method 5,6 according to the card-agglutination test for trypanosomiasis antigen procedures, 7 and recommended the DAT for clinical work in hospitals and health centers, 5 for seroepidemiologic studies, 5,8 and for mass VL population screening. 6,8 Several investigators reported high accuracy of the test under laboratory conditions for VL due to Leishmania donovani, [9][10][11] as well as L. infantum.…”
mentioning
confidence: 99%
“…The DAT was carried out essentially as described. 15 Antigen for the test was prepared from trypsin-treated, Coomassie brilliant blue-stained, formalinpreserved promastigotes of L. donovani AG83. Agglutination was carried out using a 1:500 dilution of patient sera in PBS containing 1% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…19 It is a simple technique with high sensitivity and specificity. 15,18 One of its major drawbacks is that it has no prognostic value for evaluating the progression of the disease. The DAT is used as a routine serologic test for VL in India, and the parameters of the test have been established under local conditions with very little false positivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation